Social Capital in Improving Community Welfare through Village-Owned Enterprises in Belun Village - Wijaya, Guruh Wahyu; Ari, Ismu Rini Dwi; Firdausiyah, Nailah (Fakultas Teknik Universitas Brawijaya, 2024)
Village-owned enterprises (BUMDes) are institutions or organizations that carry out activities or businesses to develop the economy in villages. The main objectives are to increase Village Own Source Revenue (PAdesa), contribute to improving community welfare, alleviate poverty, and reduce unemployment. However, according to Belun Village APBdes data, BUMDes